ANALISIS FAKTOR BAURAN PEMASARAN YANG MEMPENGARUHI KEPUASAN NASABAH SEHINGGA TERCIPTA WORD OF MOUTH POSITIF DI PT. BANK MUAMALAT INDONESIA, TBK CABANG MEDAN - Suryani Suryani (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2013)
This study attempts to determine the effect of customer satisfaction in the context of the marketing mixof positive word of mouth customers of PT. Bank Muamalat Indonesia, Tbk Medan Branch. Number of questionnaires was collected as many as 50 questionnaires respondent. Analysis technique used was factor analysis followed by discriminant analysis with program of SPSS version 17.0. Based on factor analysis, it is known that one factor called location was proved to be inaccurate (correlation value 0.5) so that it is excluded from the model. Canonical correlation is obtained for 0.593 with a significance of 0.003. It can be concluded that 35.20% of the variation of positive word of mouth can be explained by the variable of discriminant Product, Promotion, Price, People, Physics and Process.